PENGETAHUAN IBU NIFAS TENTANG KUNJUNGAN ULANG MASA NIFAS DI PUSKESMAS TEPUS 1 KABUPATEN GUNUNGKIDUL - Ekawati, Ekawati; Haniah, Haniah (Pusat Penelitian dan Pengabdian kepada Masyarakat FKes Universitas Jenderal Achmad Yani Yogyakarta, 2017)
Background: The causes of Maternal Mortality Rate (MMR) in Indonesia are bleeding (30.3%), hypertensive disorder during pregnancy (27.1%), infection (7.3%), obstructed (1.8%) and abortion (1.6%). Bleeding occurs in the postpartum period which is started after delivering placenta and ended when the the womb organs recovered as before pregnant. The length of postpartum period is about 6 weeks. During postpartum period, there are several re-visit to heath provider such as; KF 1 (first postpartum visit) is a visit on 6 hours to day 3rd after delivering, KF 2 (Second postpartum visit) is a visit on day 4th to 28th after delivering, and KF 3 (third postpartum visit) is a visit on day 29th-42nd after delivering. Objective: This study aimed to describe the knowledge level of postpartum mother about visitation during childbirth. Method: This study was a descriptive quantitative research with cross sectional design. The number of sample was 30 respondents. The data were taken using primary data and questionnaires. Result: The postpartum mother who do postpartum visits in Puskesmas Tepus 1 Gunung in the age of 20-35 years category was 19 respondents (63.3%). A number of 13 respondents (43.3%) had secondary school, 19 respondents (63.3%) were housewife and 18 respondents (60%) had 2-3 children. The result of postpartum revisit showed that 13 respondents (43.3%) made KF1, 12 respondents (40%) made KF 2, and 11 respondents (36.7%) made KF 3. Conclusion: The knowledge level of postpartum revisit in Puskesmas Tepus 1 Gunung was mostly in adequate category. Key word: Postpartum Mother Knowledge, Postpartum Visits